Harmonisasi Nilai-Nilai Pancasila dan Agama Dalam Membentuk Karakter - Abdullah Zaini (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
Character education has recently been a highly significant topic in the field of education, particularly in light of the growing phenomena of moral degeneration in society and the government environment. Pancasila and religion are two important components that have a central role in shaping individual and community character. Both work hand in hand in creating quality character. Pancasila is the main pillar that reflects the basic values that should be held by every citizen. Religion also has a significant role as a way of life that guides the actions and moral values of individuals. The deviations regarding attitudes and behavior that appear are actually the result of failure to implement the values contained in Pancasila. On the other hand, religion has not yet become a source of moral inspiration. In fact, morality has not become a guide for the majority of society and also for leaders. Therefore, greater efforts are needed in re-echoing the nation's moral affirmation which is based on belief as the nickname given to the Indonesian nation as a religious nation. This article is to deliver readers with a deep understanding of the harmonization of Pancasila and religious values in shaping character.